Discoloration of Roots Caused by Residual Endodontic Intracanal Medicaments - Belinda Kuan-Jung Chen; Roy George; Laurence James Walsh (The Scientific World Journal)
Aims. This study examined the extent to which intervisit corticosteroid-based antibiotic pastes (CAP) medicaments contribute to staining of tooth structure after attempted removal by irrigation techniques. Methods. A total of 140 roots were prepared and the canals were filled with Ledermix paste (demeclocycline), Odontopaste (clindamycin), and Doxypaste (doxycycline). The pastes were removed after 2 or 4 weeks of storage in the dark using EDTA and NaOCl with either a 27-gauge-slotted needle or an EndoActivator (Dentsply). The roots were then exposed to an intense light source for 30 minutes each week and photographed after a further 1, 3, or 6 months. Digital images were standardized and data for changes in luminosity were analysed using repeated measures ANOVA and a post hoc test. Results. Removal of the medicament did not prevent later discolouration. There was no significant difference between the paste removal methods. Ledermix paste caused the greatest darkening compared to the untreated controls, for both application periods and both methods of removal. Doxypaste and Odontopaste caused less darkening than Ledermix. Conclusion. Medicaments that stain teeth may continue to discolour teeth despite best attempts to remove them. This study stresses the importance of material selection and minimising contact of Ledermix within the coronal aspects of teeth.